Analysis of the prevalence and risk factors of osteoarthritis in a population - O. O. Portyannikova; S. M. Tsvinger; A. V. Govorin; E. N. Romanova (Современная ревматология)
The review contains data from large-scale foreign and Russian studies of the epidemiology of osteoarthritis (OA). It considers the role of modifiable and non-modifiable risk factors for OA, such as age, sex, hormonal status, obesity, etc. There are data on genetic susceptibility to OA and on congenital anomalies that contribute to joint structural changes. Data on the impact of racial and ethnic factors on the development and progression of OA are analyzed. The role of metabolic disorders in the pathogenesis of this disease is highlighted. Data on the relationship of OA to patients' professional activities are summarized.